Reading (in) a quadriform cosmos: Gospel Books in the Early Christian bibliographic imagination - Coogan, J (Johns Hopkins University Press, 2023)
Christian thinkers developed the widespread linguistic cosmology of the ancient Mediterranean in a novel way in order to advance a specific bibliographic project. Numerous early Christians throughout the Roman Mediterranean aligned the emergent fourfold Gospel with the structure of the physical cosmos. Employing interlocking concepts from the disciplines of meteorology, geography, music, mathematics, and astronomy, a number of figures—including Irenaeus, Origen, Ephrem, Eusebius, Fortunatianus, Augustine, and Maximus—imagined a Gospel corpus consisting of precisely four texts. The category of number provided a way to articulate the coherence of the fourfold Gospel—both with itself and with the rest of the world. By situating both familiar and neglected evidence in the context of ancient cosmology, I argue that early Christians theorized a divinely-ordained correspondence between fourfold Gospel and quadriform cosmos.